Building common knowledge at the boundaries between professional practices: Relational agency and relational expertise in systems of distributed expertise - Edwards, A (2011)
The article develops an earlier account of relational agency (IJER 2005). Its starting point is a view of practices as knowledge-laden and emotionally freighted sites of purposeful and expert activity. Arguments therefore draw on cultural historical analyses of activities, practices and the institutions that shape them. Relational agency in inter-professional activities is seen to be mediated by common knowledge which is built in interactions at the points where the boundaries of practices intersect. The focus will be the development of common knowledge, described by Carlile (2004, p. 557) as a capacity to 'represent the differences now of consequence and the ability of the actors involved to use it', at the sites of intersecting practices. The argument, supported by evidence from four recent studies of interprofessional work, is that building and using common knowledge is an important feature of the relational expertise required for working across the practice boundaries on complex tasks. © 2011 Elsevier Ltd.